1999
DOI: 10.4098/at.arch.99-2
|View full text |Cite
|
Sign up to set email alerts
|

Diet of a Piedmont population of Ctenomys mendocinus (Rodentia, Ctenomyidae): seasonal patterns and variations according sex and relative age

Abstract: Puig S., Rosi M. I., Cona M. I., Roig V. G. and Monge S. A. 1999. Diet of a Piedmont population of Ctenomys mendocinus (Rodentia, Ctenomyidae): seasonal patterns and variations according sex and relative age. Acta Theriologica 44: 15-27.Dietary composition was determined seasonally in males and females of Ctenomys mendocinus Philippi, 1869 from the Andean Piedmont (Mendoza, Argentina) during the reproductive and non-reproductive period. Reproductive condition and relative age of each animal was determined. Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…C. mendocinus lives in Midwestern Argentina. Although this species has generalist habits, a preference for some food items was observed, mainly represented by above-ground parts of grasses, even in populations inhabiting environments with low food availability and harsh climatic conditions (Puig et al, 1999;Rosi et al, 2003). C. eremophilus has generalist behavior with a preference on aerial vegetative part of grasses, but in grazed paddocks their diet showed lower percentage of grasses and higher dietary diversities compared with ungrazed paddocks, which was associated with the competition for grasses with cattle (Rosi et al, 2009).…”
Section: Generalist Vs Specialist Habitsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. mendocinus lives in Midwestern Argentina. Although this species has generalist habits, a preference for some food items was observed, mainly represented by above-ground parts of grasses, even in populations inhabiting environments with low food availability and harsh climatic conditions (Puig et al, 1999;Rosi et al, 2003). C. eremophilus has generalist behavior with a preference on aerial vegetative part of grasses, but in grazed paddocks their diet showed lower percentage of grasses and higher dietary diversities compared with ungrazed paddocks, which was associated with the competition for grasses with cattle (Rosi et al, 2009).…”
Section: Generalist Vs Specialist Habitsmentioning
confidence: 99%
“…Distinct foraging strategies between males and females were described in rodents, and were mainly associated to differences in nutritional requirements during the growth and reproduction stages (Puig et al, 1999). The microhistological analysis of the diet of C. mendocinus demonstrated that males have a more varied diet in winter, attributed to changes in the behavior during the beginning of the reproductive season, while females showed a higher specialization on grasses in spring, probably associated to the high energetic costs of pregnancy and lactation occurring during this period of the year (Puig et al, 1999).…”
Section: Generalist Vs Specialist Habitsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lower food availability for C. mendocinus would be expected in environments with lower plant abundance and complexity, taking into account that this rodent has been identified as a generalist herbivore in other environment of the Andean Piedmont (Madoery 1993, Puig et al 1999. These researches revealed that this rodent diet included most plant categories presented (grasses, forbs, succulents and shrubs).…”
Section: Burrow Systems In Different Plant Communitiesmentioning
confidence: 99%